Reduced GABAergic inhibition and impaired synapse elimination by neuroligin-2 deletion from Purkinje cells of the developing cerebellum - Lai, Esther Suk King; Uesaka, Naofumi; Miyazaki, Taisuke; Hashimoto, Kouichi; Watanabe, Masahiko; Kano, Masanobu (Frontiers in Neural Circuits, 2025)
Functionally mature neural circuits are shaped during postnatal development by eliminating redundant synapses formed around birth. This process is known as synapse elimination and requires a proper balance of excitation and inhibition. Neuroligin-2 (NL2) is a postsynaptic cell adhesion molecule required for the formation, maintenance, and function of inhibitory synapses. However, how NL2 regulates synapse elimination during postnatal development is largely unknown. Here we report that the deletion of NL2 from Purkinje cells (PCs) in the cerebellum impairs the developmental elimination of redundant climbing fiber (CF) to PC synapses. In global NL2-knockout (KO) mice, GABAergic inhibition to PCs was attenuated and CF synapse elimination was impaired after postnatal day 10 (P10). These phenotypes were restored by the expression of NL2 into PCs of NL2-KO mice. Moreover, microRNA-mediated knockdown of NL2 specifically from PCs during development caused attenuated inhibition and impaired CF synapse elimination. In PCs innervated by “strong” and “weak” CFs, calcium transients elicited by “weak” CFs were enhanced in NL2-deficient PCs, suggesting that excess calcium signaling permits the survival of redundant “weak” CF synapses. We conclude that NL2 is crucial for maintaining inhibitory synaptic function and properly eliminating redundant CF synapses during postnatal development.